Postsecondary Participants’ Beliefs About International Agricultural Issues - Seth Jordan; Gary Wingenbach; C. Cameron Baker; Rafael Landaverde (Social Sciences)
Teaching university students about international food and agricultural issues is paramount to preparing a globally competent workforce. Given future demands for foodstuffs needed to sustain a global populace exceeding nine billion, educators are tasked with promoting understanding of international agricultural issues. Studying students’ beliefs about international agriculture and the information sources and experiences used to form those beliefs is necessary in preparing a globally competent workforce. The purpose of this study was to explore university participants’ beliefs about international agriculture issues and the information sources and experiences used to learn about such issues using a cross-sectional design with random samples at Texas A&M University. Results showed that beliefs about international agriculture issues were strong; graduate students held the strongest beliefs. Those with an international experience, family in agriculture, or majors in agriculture held stronger beliefs about the diversity of international agriculture. Respondents with international experience(s) perceived internal and external sources and experiences as beneficial to learning about international agricultural issues. Efforts to create a more inclusive curriculum for international agricultural issues can be enhanced through specific information sources and experiences in postsecondary education. Research is needed to explore complex factors (e.g., educator–learner and peer-to-peer homophily, experience abroad) affecting beliefs about international agricultural issues.